PENGARUH STRATEGI PEMECAHAN MASALAH SISTEMATIS BERBANTUAN SOLUTION PATH OUTLINE (SPO) TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMAN 2 BATANG KAPAS - Afriyola Saputra (PILLAR OF PHYSICS EDUCATION, 2013)
One strategy that can be used by teachers to solve this problem is to use systematic problem solving strategy assisted solution path outline (SPO). This research aimed to investigate the influence of systematic problem solving strategy assisted SPO to physics learning result of student grade X SMAN 2 Batang Kapas. Type of this research is Quasi Experiment with randomized control group only design. The population of research was all student in grade X SMAN 2 Batang Kapas that enrolled in the academic year 2012/2013. The research samples were determined through cluster sampling technique, grades choiced as research sample were X1 and X3.. Base on data analysis, in experimental class was higher than control class, which the average value of experimental class was 83.85 and the of control class was 78.21.Meanwhile, in affective domain was gotten the average value of experimental class 79.88 and the of control class 71.82. The hypothesis was tested by t-tested, in cognitive domain tcount=2,48 and in affective domain tcount=4,28 in the real level 0.05, means tcount>ttable. Thus work hypothesis was acceptable. The conclusion of this research is implementation of problem solving strategy assisted solution path ouline (SPO) increased Physics learning result of student grade X SMAN 2 Batang Kapas. . Keywords : critical thinking, learning result, solution path outline (spo), systematic problem solving strategies